Conductive material dispersed solution, electrode and lithium secondary battery prepared by using the same

KR103030382B1Active Publication Date: 2026-10-13LG ENERGY SOLUTION LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
KR1020240130081
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-09-25
Filing Date
2024-09-25
Publication Date
2026-10-13
Estimated Expiration
2044-09-25
Patent Text Reader

Abstract

The present invention relates to a conductive dispersion comprising single-walled carbon nanotube (SWCNT) clusters, wherein the number average length of the SWCNT clusters is 0.8 μm to 8.0 μm, and SWCNT clusters with a length exceeding 10 μm account for 15% or less of the total number, and the number average diameter is 5 nm to 30 nm, and SWCNT clusters with a diameter exceeding 30 nm account for 15% or less of the total number, and the length and diameter of the SWCNT clusters are measured using an atomic force microscope (AFM), and an electrode comprising said SWCNT clusters. The invention has the advantage of being able to secure excellent conductivity with a small amount by forming a conductive network well due to excellent dispersibility, and having excellent porosity due to the low viscosity of the dispersion, and when said conductive dispersion is applied to an electrode, it can contribute to improving the performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a conductive material dispersion comprising SWCNT clusters with limited length and diameter characteristics, an electrode to which the dispersion is applied, and a lithium secondary battery. Background Technology

[0003] Due to the rapid increase in the use of fossil fuels, there is a growing demand for alternative or clean energy. As part of this effort, the fields of power generation and energy storage utilizing electrochemical reactions are the most actively researched.

[0004] Currently, a representative example of an electrochemical device utilizing such electrochemical energy is the secondary battery, and its scope of application is increasingly expanding. Recently, with the technological development and growing demand for portable devices such as portable computers, mobile phones, and cameras, the demand for secondary batteries as an energy source has been rapidly increasing. Among these secondary batteries, much research has been conducted on lithium secondary batteries, which have high energy density—that is, high capacity—and have been commercialized and are widely used.

[0005] The electrode of a secondary battery comprises an electrode active material, a conductive material, and a binder. Carbon nanotubes can be used as the conductive material to improve the conductivity of the electrode; in particular, when a material with a large specific surface area is applied, the conductivity improvement effect is excellent even when using a small amount.

[0006] When single-walled carbon nanotubes (SWCNTs) are used as carbon nanotubes, the resistance of the electrode can be further lowered, and since the specific surface area is relatively large, it is easy to secure conductivity with only a small amount. In order for the single-walled carbon nanotubes to be uniformly distributed within the electrode, when manufacturing the electrode, a conductive material dispersion solution in which the single-walled carbon nanotubes are dispersed is first formed, and then an electrode slurry is prepared using the conductive material dispersion solution.

[0007] However, single-walled carbon nanotubes have a problem in that the improvement in battery performance varies significantly depending on their dispersibility and intrinsic properties, and there is also a problem where discrepancies occur in evaluation because the dispersibility expected from values ​​measured in the conductive material dispersion does not directly correlate with the degree of distribution within the electrode.

[0008] Therefore, when applying single-walled carbon nanotubes as conductive materials for electrodes, there is a need for research on conductive material dispersions that exhibit excellent properties in the dispersion state and allow for the intuitive prediction of electrode performance through dispersion evaluation, as these properties are directly reflected in the electrode. The problem to be solved

[0010] One objective according to the present invention is to provide a conductive material dispersion with excellent dispersibility and low viscosity, and excellent processability, by applying a single-walled carbon nanotube (SWCNT) cluster, which is an aggregate of single-walled carbon nanotubes that are relatively short in length and small in diameter, while minimizing the proportion of SWCNT clusters that are long in length and large in diameter, and applying SWCNT clusters characterized by a wide distribution of number average length and number average diameter distributions among SWCNT clusters that are relatively short in length and thin in diameter.

[0011] Another objective according to the present invention is to provide an electrode with excellent resistance characteristics in which a conductive network is well formed when the conductive material dispersion is applied to the electrode.

[0012] Another objective according to the present invention is to provide a lithium secondary battery with excellent output and improved lifespan due to low resistance by including an electrode with excellent conductivity and maintenance performance. means of solving the problem

[0014] [1] According to one embodiment of the present invention, a conductive dispersion is provided that comprises single-walled carbon nanotube (SWCNT) clusters, wherein the SWCNT clusters have a number average length of 0.8 μm to 8.0 μm, and SWCNT clusters with a length exceeding 10 μm account for 15% or less of the total number, and SWCNT clusters with a diameter exceeding 30 nm account for 15% or less of the total number, and the length and diameter of the SWCNT clusters are measured using an atomic force microscope (AFM).

[0015] [2] In the above [1], the SWCNT cluster may have a number average length of 1.0 μm to 6.0 μm.

[0016] [3] In the above [1] and / or [2], the SWCNT cluster may have single-walled carbon nanotubes with a number average length of more than 10 μm that make up 10% or less of the total number.

[0017] [4] In at least one of [1] to [3] above, the SWCNT cluster may have a number average diameter of 7 nm to 20 nm.

[0018] [5] In at least one of [1] to [4] above, the SWCNT clusters may have SWCNT clusters with a diameter exceeding 30 nm that make up 10% or less of the total number.

[0019] [6] In at least one of [1] to [5] above, the conductive material dispersion further comprises a dispersant, and the dispersant may comprise one or more selected from the group consisting of polyacrylate, polyvinylidene fluoride (PVDF), polyvinylpyrrolidone (PVP), polyvinyl alcohol, polyacrylamide, polyethylene oxide, carboxymethyl cellulose (CMC), and diisopropylamine (DIPA).

[0020] [7] In the above [6], the conductive material dispersion may comprise 0.2 to 3.5 parts by weight of SWCNT clusters and 0.2 to 7.0 parts by weight of a dispersant with respect to 100 parts by weight of the dispersion.

[0021] [8] According to another embodiment of the present invention, an electrode active material layer comprising an electrode active material, a single-walled carbon nanotube (SWCNT) cluster, and a binder is disposed on a current collector, wherein the number average length of the SWCNT cluster is 0.8 μm to 8.0 μm, and the number of SWCNT clusters with a length exceeding 10 μm is 15% or less of the total number, and the number average diameter is 5 nm to 30 nm, and the number of SWCNT clusters with a diameter exceeding 30 nm is 15% or less of the total number, and the length and diameter of the SWCNT cluster are measured using an atomic force microscope (AFM).

[0022] [9] In the above [8], the electrode active material is a positive electrode active material, and the positive electrode active material may comprise one or more selected from the group consisting of lithium nickel-ternary oxide, lithium manganese oxide, lithium iron phosphate, lithium nickel oxide, lithium cobalt oxide and lithium manganese oxide.

[0023]

[10] In the above [8] and / or [9], the electrode active material is a negative electrode active material, and the negative electrode active material may comprise one or more selected from the group consisting of carbon-based particles, silicon-based particles and carbon-silicon-based composite particles.

[0024]

[11] In at least one of [8] to

[10] above, the electrode further comprises a point-shaped conductive material, and the point-shaped conductive material may comprise carbon black.

[0026]

[12] According to another embodiment of the present invention, a lithium secondary battery is provided having a structure in which a positive electrode, a separator, and a negative electrode are stacked sequentially, and at least one of the positive electrode and the negative electrode is the aforementioned electrode. Effects of the invention

[0028] The conductive material dispersion according to the present invention comprises SWCNT clusters having unique length and diameter characteristics, and thus has excellent dispersibility and low viscosity, and excellent storage stability due to the small change in viscosity over time, and thus processability can be improved.

[0029] Accordingly, by applying an SWCNT cluster having the above characteristics to an electrode slurry, the phase stability of the slurry can be improved, and since it has excellent dispersibility, sufficient conductivity can be secured even with a small amount, thereby enabling the realization of an electrode with excellent resistance characteristics. In addition, by applying an electrode with excellent resistance characteristics as described above, the output of the lithium secondary battery can be improved, and not only is a conductive network well formed, but the retention force is also excellent, which can contribute to the improvement of the lifespan of the lithium secondary battery. Specific details for implementing the invention

[0031] Terms and words used in this specification and claims should not be interpreted as being limited to their ordinary or dictionary meanings, but should be interpreted in a meaning and concept consistent with the technical spirit of the invention, based on the principle that the inventor can appropriately define the concept of the terms to best describe his invention.

[0032] In this specification, terms such as “comprising,” “comprising,” or “having” are intended to specify the existence of the implemented features, numbers, steps, components, or combinations thereof, and do not exclude the existence or addition of one or more other features, numbers, steps, components, or combinations thereof.

[0033] In this specification, the volume cumulative average particle size D 50 and D 90 In the particle size distribution curve of silver particles, they can be defined as the particle sizes corresponding to 50% and 90% of the cumulative volume, respectively. The above D 50 and D 90 For example, it can be measured using the laser diffraction method. The laser diffraction method generally enables the measurement of particle sizes ranging from the submicron range to several millimeters, and can obtain results with high reproducibility and high resolution.

[0034] In this specification, the number average length and diameter of carbon nanotubes and the ratio of length exceeding 10 μm and diameter exceeding 30 nm can be derived by obtaining the number cumulative length and diameter distribution map by obtaining the lengths and diameters of more than 400 carbon nanotubes through images measured at magnifications of 20 μm x 20 μm, 15 μm x 15 and / or 10 μm x 10 μm using an atomic force microscope (AFM) (Asylum Research, Cypher ES AFM System) on carbon nanotubes in AC Air Topography mode (Tapping mode) under conditions of Set point 0.4 V and Scan rate 1.5 Hz.

[0035] In this specification, the term "cluster" may refer to a form in which a plurality of units are combined to form a single aggregate, and a single-walled carbon nanotube (SWCNT) cluster may refer to an aggregate or collection in which a plurality of SWCNT units are combined to form a single fiber.

[0037] The present invention will be described in detail below.

[0038] In this specification, each of the conductive material dispersion, electrode, and lithium secondary battery comprises one or more of the technical features and / or technical configurations described below, and these technical features and / or technical configurations may be combined in various ways.

[0040] Dispersed conductive material

[0041] A conductive material dispersion according to one embodiment of the present invention comprises single-walled carbon nanotube (SWCNT) clusters, wherein the number average length of the SWCNT clusters is 0.8 μm to 8.0 μm, and SWCNT clusters with a length exceeding 10 μm account for 15% or less of the total number, and the number average diameter is 5 nm to 25 nm, and SWCNT clusters with a diameter exceeding 30 nm account for 15% or less of the total number, and the length and diameter of the SWCNT clusters are measured using an atomic force microscope (AFM).

[0043] (1) Single-walled carbon nanotube

[0044] Carbon nanotubes consist of graphite sheets having a cylindrical shape with a nano-sized diameter and an sp2 bonding structure; they exhibit conductive or semiconductor properties depending on the rolling angle and structure of the graphite sheets. Carbon nanotubes can be classified into single-walled carbon nanotubes (SWCNT), double-walled carbon nanotubes (DWCNT), and multi-walled carbon nanotubes (MWCNT) based on the number of bonds forming the walls.

[0046] According to one embodiment of the present invention, the conductive material dispersion comprises SWCNT clusters, which are aggregates of single-walled carbon nanotubes (SWCNT). Since single-walled carbon nanotubes have a larger specific surface area compared to multi-walled carbon nanotubes, sufficient conductivity can be ensured even with only a small amount added, thereby significantly increasing the reduction in electrode resistance. However, in order to maximize the advantage that conductivity can be easily secured even with only a small amount of single-walled carbon nanotubes, it is necessary for them to have excellent length characteristics. However, it is not easy to accurately measure the length characteristics, and often the expected degree of conductivity improvement does not appear as expected. Furthermore, even if the length characteristics are good, there is a problem that if they are excessive, they can affect the viscosity of the dispersion and, furthermore, the viscosity of the slurry.

[0048] Accordingly, the inventors intend to provide a conductive dispersion containing SWCNT clusters having limited length and diameter characteristics and unique features, which allows for intuitive prediction of the ability to form a conductive path within an electrode through these measurements, while ensuring excellent dispersibility without increasing the viscosity of the dispersion.

[0049] SWCNT clusters included in a conductive material dispersion according to one embodiment of the present invention have a number average length of 0.8 μm to 8.0 μm, and SWCNT clusters with a length exceeding 10 μm account for 15% or less of the total number, and the number average length of the SWCNT clusters and the ratio of the number of SWCNT clusters with a length exceeding 10 μm can be derived through the number distribution obtained through the aforementioned atomic force microscope measurement.

[0050] The above SWCNT cluster has an appropriate length satisfying a number average length of 0.8 μm to 8.0 μm, and is characterized by excluding SWCNT clusters with a long length exceeding 10 μm. Additionally, within the range satisfying the number average length, the conductive network formed can be well maintained even with the volume expansion of the electrode occurring during the charge-discharge cycle.

[0051] According to one embodiment of the present invention, the SWCNT cluster has a number average length of 0.8 μm to 8.0 μm, preferably 0.9 μm or more, 1.0 μm or more, 1.1 μm or more, 1.2 μm or more, 1.3 μm or more, 1.4 μm or more, or 1.5 μm or more, and 7.8 μm or less, 7.5 μm or less, 7.0 μm or less, 6.5 μm or less, 6.0 μm or less, 5.5 μm or less, 5.0 μm or less, 4.5 μm or less, or 4.0 μm or less. If the number average length is less than 0.8 μm, the length is too short, and it may not be easy to maintain the conductive network connection path due to the volume change of the electrode caused by charging and discharging. In addition, if the number average length exceeds 8.0 μm, the number of SWCNT clusters per unit weight decreases, while the viscosity of the dispersion increases and the distribution within the electrode becomes uneven.

[0052] In addition, according to one embodiment of the present invention, the SWCNT clusters are characterized in that SWCNT clusters with a length exceeding 10 μm account for 15% or less of the total number, and preferably, 13% or less, 11% or less, 10% or less, or 9% or less. Once the number of SWCNT clusters exceeding 10 μm exceeds 15%, it becomes impossible to control the viscosity of the dispersion, and even if the dispersion conditions are adjusted to achieve uniform dispersion, the likelihood of severe changes in viscosity over time may increase rapidly. Furthermore, as the number of long SWCNT clusters increases, it becomes more difficult to achieve a uniform distribution within the electrode, and since there is a high possibility that the prediction for securing conductivity measured in the dispersion will not be intuitively reflected in the electrode state, the control of the number of SWCNT clusters exceeding 10 μm in length needs to be performed precisely.

[0053] SWCNT clusters included in a conductive material dispersion according to one embodiment of the present invention are characterized by having a number average diameter of 7 nm to 20 nm, and SWCNT clusters with a diameter exceeding 30 nm being 10% or less of the total number, and the number average diameter of the SWCNT clusters and the ratio of the number of SWCNT clusters with a diameter exceeding 30 nm can be derived through the number distribution obtained through the aforementioned atomic force microscope measurement.

[0054] The above SWCNT cluster has an appropriate diameter satisfying a number average diameter of 7 nm to 20 nm, and is characterized by excluding an excess of SWCNT clusters with a thick diameter exceeding 30 nm. Additionally, within the range satisfying the number average diameter, the conductive network formed can be well maintained even with the volume expansion of the electrode occurring during the charge-discharge cycle.

[0055] According to one embodiment of the present invention, the SWCNT cluster has a number average diameter of 7 nm to 20 nm, preferably 8 nm or more, 9 nm or more, 10 nm or more, 11 nm or more, or 12 µm or more, and 19 nm or less, 18 nm or less, 17 nm or less, 16 nm or less, or 15 nm or less. If the number average diameter is smaller than 7 nm, the diameter is too thin, so the SWCNT cluster may be easily damaged during charging and discharging, and problems such as disconnection due to volume expansion may occur, making it difficult to maintain the conductive network connection path. In addition, if the number average diameter exceeds 20 nm, the number of SWCNT clusters per unit weight decreases while the viscosity of the dispersion increases, and problems may arise such as poor dispersion resulting in uneven distribution within the electrode, and if attached to the surface of the active material, it may act as a factor that hinders the mobility of lithium ions.

[0056] According to one embodiment of the present invention, the SWCNT clusters are characterized by SWCNT clusters with a length exceeding 30 nm being 10% or less of the total number, preferably 9% or less, 8% or less, or 7% or less. Once the number of SWCNT clusters with a diameter exceeding 30 nm exceeds 10%, it becomes impossible to control the viscosity of the dispersion, and even if the dispersion conditions are adjusted to achieve uniform dispersion, the likelihood of severe changes in viscosity over time may increase rapidly. Furthermore, as the number of SWCNT clusters with a large diameter increases, it becomes more difficult to achieve a uniform distribution within the electrode, and as mentioned above, it is highly likely to act as a factor hindering the mobility of lithium ions; therefore, the number of SWCNT clusters with a diameter exceeding 30 nm needs to be controlled precisely.

[0057] Typically, in the case of a conductive material dispersion containing carbon nanotubes, the volume-cumulative average particle size (D) of the dispersion is used to predict the formation of a conductive path and uniform distribution at the electrode. 50 and / or D 90 Although it is common to utilize the particle size distribution in such a dispersion state, the particle size distribution does not accurately reflect the actual length and diameter of the carbon nanotubes or their aggregates, so there have been cases where the performance of the electrode differs even when the same particle size distribution is applied. However, the length and diameter characteristics obtained from the number cumulative length and diameter distribution through atomic force microscope images according to one embodiment of the present invention appear substantially the same in the dispersion state and in the electrode, so they can be more effective and intuitive in improving the performance of the electrode.

[0059] According to one embodiment of the present invention, the SWCNT cluster may be included in an amount of 0.2 to 3.5 parts by weight per 100 parts by weight of the conductive material dispersion, specifically in an amount of 0.2 to 3.0 parts by weight. When the above range is satisfied, high productivity is maintained while the transfer and input of the electrode slurry are easy. In addition, since the solid content of the manufactured electrode slurry does not become excessively low, binder migration during electrode drying can be suppressed. Accordingly, electrode adhesion can be improved, and packing of the electrode active material layer is effectively achieved, allowing for the manufacture of a low-thickness electrode.

[0061] (2) Dispersant

[0062] A conductive material dispersion according to one embodiment of the present invention may further include a dispersant, and the dispersant may include one or more selected from the group consisting of polyacrylate, polyvinylidene fluoride (PVDF), polyvinylpyrrolidone (PVP), polyvinyl alcohol, polyacrylamide, polyethylene oxide, hydrogenated nitrile copolymer, cellulose-based compound, and diisopropylamine (DIPA). Here, the hydrogenated nitrile copolymer may be hydrogenated acrylonitrile-butadiene rubber, and the cellulose-based compound may be carboxymethyl cellulose (CMC) or hydroxyethyl cellulose (HEC).

[0063] In addition, the dispersant may be included in the conductive material dispersion in an amount of 0.2 to 7.0 parts by weight, specifically 0.2 to 6.0 parts by weight, and more specifically 0.3 to 5.0 parts by weight, per 100 parts by weight of the conductive material dispersion. When the above range is satisfied, the carbon-based conductive material can be smoothly dispersed within the conductive material dispersion, and the energy density of the manufactured electrode can be improved and the resistance reduced.

[0065] (3) solvent

[0066] According to one embodiment of the present invention, the conductive material dispersion may further comprise a solvent, the solvent comprises water or an organic solvent, and the organic solvent may comprise one or more heteroatoms selected from the group consisting of nitrogen atoms (N) and oxygen atoms (O) having non-covalent electron pairs.

[0067] Specifically, the organic solvent is an amide-based polar organic solvent such as dimethylformamide (DMF), diethylformamide, dimethylacetamide (DMAc), or N-methylpyrrolidone (NMP); alcohols such as methanol, ethanol, 1-propanol, 2-propanol (isopropyl alcohol), 1-butanol (n-butanol), 2-methyl-1-propanol (isobutanol), 2-butanol (sec-butanol), 1-methyl-2-propanol (tert-butanol), pentanol, hexanol, heptanol, or octanol; glycols such as ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, 1,3-propanediol, 1,3-butanediol, 1,5-pentanediol, or hexylene glycol; and polyhydric alcohols such as glycerin, trimethylolpropane, pentaerythritol, or sorbitol. Examples include glycol ethers such as ethylene glycol monomethyl ether, diethylene glycol monomethyl ether, triethylene glycol monomethyl ether, tetraethylene glycol monomethyl ether, ethylene glycol monoethyl ether, diethylene glycol monoethyl ether, triethylene glycol monoethyl ether, tetraethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monobutyl ether, triethylene glycol monobutyl ether, or tetraethylene glycol monobutyl ether; ketones such as acetone, methyl ethyl ketone, methylpropyl ketone, or cyclopentanone; esters such as ethyl acetate, γ-butyl lactone, and ε-propiolactone, and any one or a mixture of two or more of these may be used. N-methylpyrrolidone (NMP) is particularly preferred when considering miscibility with the electrode slurry.

[0069] (4) Others

[0070] According to one embodiment of the present invention, in the conductive material dispersion, the solid content of the conductive material dispersion may be 0.3 wt% to 7.0 wt%, specifically 0.4 wt% to 5.0 wt%, and more specifically 0.5 wt% to 3.5 wt%. When the above range is satisfied, the viscosity of the conductive material dispersion can be maintained at a low level, while the dispersion of the conductive material dispersion can be effectively achieved. Here, solid content may refer to SWCNT clusters and dispersants contained in the conductive material dispersion.

[0072] The conductive material dispersion of the present invention, comprising the above-described components, can be prepared by mixing SWCNT clusters, a dispersant, and a solvent. At this time, the mixing can be performed using a conventional mixing method, specifically using a mixing device such as a homogenizer, a bead mill, a ball mill, a basket mill, an attrition mill, a universal stirrer, a clear mixer, a spike mill, or a TK mixer, and the order of mixing each component is not particularly limited. That is, the conductive material dispersion according to the present invention can be prepared by adding single-walled carbon nanotubes (e.g., in a large bundle state at the micro level) to a solvent and then adding a dispersant to mix; by adding the dispersant to the solvent first and then mixing the single-walled carbon nanotube bundles; or by adding the single-walled carbon nanotube bundles and the dispersant together to the solvent and then mixing.

[0073] Meanwhile, cavitation dispersion treatment may be performed to enhance the dispersibility of single-walled carbon nanotube bundles during the above mixing process. The cavitation dispersion treatment is a dispersion method that utilizes shock waves generated by the rupture of vacuum bubbles formed in water when high energy is applied to a liquid, and by this method, single-walled carbon nanotubes can be dispersed into SWCNT clusters without damaging their properties. Specifically, the cavitation dispersion treatment may be performed by ultrasound, a jet mill, or a shear dispersion treatment.

[0075] According to one embodiment of the present invention, the conductive material dispersion may further include point-shaped conductive materials. The conductive material that may be additionally included has characteristics different from the SWCNT cluster having the aforementioned characteristics, and it may be preferable that its shape characteristics are different. If a conductive material with similar shape characteristics, such as a linear conductive material like a multi-walled carbon nanotube or carbon nanofiber, is included, it may affect the formation of a conductive network due to the characteristics of the SWCNT cluster described above.

[0076] For example, the point-type conductive material may include carbon black, and the carbon black may include one or more selected from the group consisting of acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal black.

[0078] electrode

[0079] An electrode according to another embodiment of the present invention comprises an electrode active material layer comprising an electrode active material, a single-walled carbon nanotube (SWCNT) cluster, and a binder disposed on a current collector, wherein the number average length of the SWCNT cluster is 0.8 μm to 8.0 μm, and SWCNT clusters with a length exceeding 10 μm account for 15% or less of the total number, and the number average diameter is 5 nm to 30 nm, and SWCNT clusters with a diameter exceeding 30 nm account for 15% or less of the total number, and the length and diameter of the SWCNT cluster are measured using an atomic force microscope (AFM).

[0081] At this time, the SWCNT cluster is the SWCNT cluster included in the conductive material dispersion according to the present invention as described above. Since the details regarding this are the same as those described above, a detailed explanation is omitted, and the remaining components are described below.

[0083] According to one embodiment of the present invention, the electrode active material may be a positive active material, and the electrode may be a positive electrode, and the positive electrode may include a positive current collector and a positive active material layer formed on the positive current collector and containing the positive active material.

[0084] In the above positive electrode, the positive current collector may be conductive without causing chemical changes in the battery, and is not particularly limited. For example, the above positive current collector may be stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc.

[0085] The above positive current collector can typically have a thickness of 3 μm to 500 μm, and preferably can have a thickness of 300 μm or less, 200 μm or less, 100 μm or less, or 80 μm or less. Fine irregularities may be formed on the surface of the current collector to strengthen the bonding force with the positive active material. For example, it can be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0086] The above-mentioned positive electrode active material may be a commonly used positive electrode active material. Specifically, the above-mentioned positive electrode active material may be a layered compound such as lithium cobalt oxide (LiCoO2) or lithium nickel oxide (LiNiO2), or a compound substituted with one or more transition metals; lithium iron oxide such as LiFe3O4; or a compound with the chemical formula Li 1+c1 Mn 2-c1 Lithium manganese oxides such as O4 (0≤c1≤0.33), LiMnO3, LiMn2O3, LiMnO2, etc.; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5, Cu2V2O7, etc.; chemical formula LiNi 1-c2 M c2 Ni-site type lithium nickel oxide or lithium nickel-ternary oxide represented by O2 (wherein M is at least one selected from the group consisting of Co, Mn, Al, Cu, Fe, Mg, B, and Ga, satisfying 0.01≤c2≤0.3); chemical formula LiMn 2-c3 M c3 Examples include lithium manganese composite oxides represented by O2 (where M is at least one selected from the group consisting of Co, Ni, Fe, Cr, Zn and Ta, satisfying 0.01≤c3≤0.1) or Li2Mn3MO8 (where M is at least one selected from the group consisting of Fe, Co, Ni, Cu and Zn); and LiMn2O4 in which a portion of the Li in the chemical formula is substituted with alkaline earth metal ions, but are not limited thereto. The anode may also be Li-metal.

[0087] Preferably, the positive electrode active material may comprise one or more selected from the group consisting of lithium nickel-ternary oxide, lithium manganese oxide, lithium iron phosphate, lithium nickel oxide, lithium cobalt oxide, and lithium manganese oxide.

[0088] The above-described positive active material layer may include a positive conductive material and a positive binder together with the positive active material described above.

[0089] At this time, the above-mentioned positive conductive material may be the aforementioned conductive material dispersion, and may be additionally included to impart conductivity to the electrode in addition to the conductive material dispersion; and in the battery being constructed, any material that possesses electronic conductivity without causing chemical changes may be used without special limitations.

[0090] Specific examples include graphite such as natural graphite or artificial graphite; carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fibers; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and one of these alone or a mixture of two or more of these may be used.

[0091] In addition, the anode binder serves to improve adhesion between anode active material particles and adhesion between the anode active material and the anode current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethylcellulose (CMC), starch, hydroxypropylcellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene butadiene rubber (SBR), fluororubber, or various copolymers thereof, and one of these alone or a mixture of two or more may be used.

[0093] According to one embodiment of the present invention, the electrode active material may be a negative electrode active material, and the electrode may be a negative electrode, and the negative electrode may include a negative electrode current collector and a negative electrode active material layer formed on the negative electrode current collector and containing the negative electrode active material.

[0094] The above-mentioned negative current collector is not particularly limited as long as it has high conductivity without causing chemical changes in the battery, and for example, copper, stainless steel, aluminum, nickel, titanium, heat-treated carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., and aluminum-cadmium alloy may be used.

[0095] The above-mentioned negative current collector can typically have a thickness of 3 μm to 500 μm, and preferably can have a thickness of 300 μm or less, 200 μm or less, 100 μm or less, or 80 μm or less. Fine irregularities may be formed on the surface of the current collector to strengthen the bonding force with the negative active material. For example, it can be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0096] As the above-mentioned negative electrode active material, a compound capable of reversible intercalation and deintercalation of lithium may be used. Specific examples include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; (quasi)metallic compounds capable of alloying with lithium, such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, or Al alloys; SiOv(0 <v≤2), SnO2, 바나듐 산화물, 리튬 바나듐 산화물과 같이 리튬을 도프 및 탈도프할 수 있는 (준)금속 산화물; 또는 Si-C 복합체 또는 Sn-C 복합체과 같이 상기 금속질 화합물과 탄소질 재료를 포함하는 복합물 등을 들 수 있으며, 이들 중 어느 하나 또는 둘 이상의 혼합물이 사용될 수 있다. 또한, 상기 음극활물질로서 금속 리튬 박막이 사용될 수도 있다. 또, 탄소재료는 저결정성 탄소 및 고결정성 탄소 등이 모두 사용될 수 있다. 저결정성 탄소로는 연화탄소 (soft carbon) 및 경화탄소 (hard carbon)가 대표적이며, 고결정성 탄소로는 무정형, 판상, 인편상, 구형 또는 섬유형의 천연 흑연 또는 인조 흑연, 키시 흑연 (Kish graphite), 열분해 탄소 (pyrolytic carbon), 액정 피치계 탄소섬유 (mesophase pitch based carbon fiber), 탄소 미소구체 (meso-carbon microbeads), 액정피치 (Mesophase pitches) 및 석유와 석탄계 코크스 (petroleum or coal tar pitch derived cokes) 등의 고온 열처리탄소가 대표적이다.

[0097] For example, the above-mentioned negative electrode active material may comprise one or more selected from the group consisting of carbon-based particles, silicon-based particles, and carbon-silicon-based composite particles. Additionally, preferably, the above-mentioned negative electrode active material may comprise a silicon-based active material, for example, Si particles, SiOv(0 <v≤2), 또는 Si-C 복합체를 포함할 수 있다.

[0098] The above-mentioned cathode active material may be included in an amount of 70% to 99% by weight based on the total solid content in the cathode slurry, and may be 75% or more, 80% or more, 85% or more, 90% or more, or 95% or more by weight, and may also be included in an amount of 99.0% or less, 98.5% or less, 98.0% or less, or 97.5% or less by weight. When the content of the cathode active material satisfies the above range, excellent energy density, electrode adhesion, and electrical conductivity can be achieved.

[0099] The above binder is intended to secure adhesion between electrode active materials or between electrode active materials and current collectors, and general binders used in the relevant technical field may be used, and the type thereof is not particularly limited. Examples of the above binders include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethylcellulose (CMC), starch, hydroxypropylcellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, or various copolymers thereof, and one of these alone or a mixture of two or more may be used.

[0100] The binder may be included in an amount of 10.0 wt% or less based on the total solid content in the cathode slurry, preferably 0.5 wt% or more, 1.0 wt% or more, 1.5 wt% or more, or 2.0 wt% or more, and may also be included in an amount of 9.0 wt% or less, 8.0 wt% or less, 7.0 wt% or less, or 5.0 wt% or less. When the content of the binder satisfies the above range, excellent electrode adhesion can be achieved while minimizing the increase in electrode resistance.

[0101] At this time, the above-mentioned cathode conductive material may be the aforementioned conductive material dispersion, and may be additionally included to impart conductivity to the electrode in addition to the conductive material dispersion; in the battery being constructed, any material that possesses electronic conductivity without causing chemical changes may be used without special limitations.

[0102] Specific examples include graphite such as natural graphite or artificial graphite; carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fibers; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and one of these alone or a mixture of two or more of these may be used.

[0104] Meanwhile, the electrode active material layer can be formed by coating an electrode slurry, in which an electrode active material, a binder, and a conductive material dispersion containing the SWCNT cluster are dispersed in a solvent, onto a current collector, followed by drying and rolling processes.

[0105] Specifically, the electrode active material layer can be formed by applying an electrode slurry onto an electrode current collector and then drying it, or by applying an electrode slurry onto a separate support and then laminating a film obtained by peeling it off from the support onto an electrode current collector. If necessary, after forming the electrode active material layer through the above method, a rolling process may be additionally performed. At this time, drying and rolling may be performed under appropriate conditions considering the physical properties of the electrode to be finally manufactured, and are not particularly limited.

[0107] The electrode slurry may additionally include a solvent as needed to control viscosity, etc. In this case, the solvent may be water, an organic solvent, or a mixture thereof. Examples of the organic solvents include amide-based polar organic solvents such as dimethylformamide (DMF), diethylformamide, dimethylacetamide (DMAc), and N-methylpyrrolidone (NMP); and alcohols such as methanol, ethanol, 1-propanol, 2-propanol (isopropyl alcohol), 1-butanol (n-butanol), 2-methyl-1-propanol (isobutanol), 2-butanol (sec-butanol), 1-methyl-2-propanol (tert-butanol), pentanol, hexanol, heptanol, or octanol. Glycols such as ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, 1,3-propanediol, 1,3-butanediol, 1,5-pentanediol, or hexylene glycol; polyhydric alcohols such as glycerin, trimethylolpropane, pentaerythritol, or sorbitol; glycol ethers such as ethylene glycol monomethyl ether, diethylene glycol monomethyl ether, triethylene glycol monomethyl ether, tetraethylene glycol monomethyl ether, ethylene glycol monoethyl ether, diethylene glycol monoethyl ether, triethylene glycol monoethyl ether, tetraethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monobutyl ether, triethylene glycol monobutyl ether, or tetraethylene glycol monobutyl ether; Examples include ketones such as acetone, methyl ethyl ketone, methylpropyl ketone, or cyclopentanone; esters such as ethyl acetate, γ-butyl lactone, and ε-propiolactone; any one or more of these may be used, but are not limited thereto.

[0108] The solvent may be included in an amount such that the solid content in the electrode slurry is 40% to 85% by weight, preferably 50% to 80% by weight. When the above range is satisfied, binder migration is suppressed, so electrode adhesion can be improved, the drying temperature can be lowered to improve coating properties, and the coating speed can be increased to improve productivity.

[0110] lithium secondary battery

[0111] A lithium secondary battery according to another embodiment of the present invention has a structure in which a positive electrode, a separator, and a negative electrode are sequentially stacked, and at least one of the positive electrode and the negative electrode is the aforementioned electrode. Specifically, the lithium secondary battery according to the present invention may include a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, wherein the positive electrode and the negative electrode are as described above.

[0112] Below, we will explain only the remaining components.

[0114] According to one embodiment of the present invention, the separator separates the negative electrode and the positive electrode and provides a pathway for the movement of lithium ions, and can be used without special limitations as long as it is used as a separator in a secondary battery. Specifically, as the separator, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminated structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of high-melting-point glass fibers, polyethylene terephthalate fibers, etc., may be used. Furthermore, a coated separator containing a ceramic component or a polymer material may be used to ensure heat resistance or mechanical strength, and may optionally be used in a single-layer or multi-layer structure.

[0116] According to one embodiment of the present invention, the electrolyte may include an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, a molten inorganic electrolyte, etc., which can be used when manufacturing a lithium secondary battery, but is not limited to these.

[0117] Specifically, the electrolyte may include a non-aqueous organic solvent and a metal salt.

[0118] As the above-mentioned non-aqueous organic solvent, for example, aprotic organic solvents such as N-methyl-2-pyrrolidinone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, gamma-butyl lactone, 1,2-dimethoxyethane, tetrahydroxyfuran, 2-methyl tetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolone, formamide, dimethylformamide, dioxolan, acetonitrile, nitromethane, methyl formate, methyl acetate, phosphate triester, trimethoxymethane, dioxolan derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ether, methyl propionate, ethyl propionate, etc. may be used.

[0119] In particular, among the above carbonate-based organic solvents, ethylene carbonate and propylene carbonate, which are cyclic carbonates, are high-viscosity organic solvents with high dielectric constants that effectively dissociate lithium salts, so they can be used preferably. Furthermore, if low-viscosity, low-dielectric constant linear carbonates such as dimethyl carbonate and diethyl carbonate are mixed with these cyclic carbonates in appropriate proportions, an electrolyte with high electrical conductivity can be produced, making it even more preferable to use.

[0120] The metal salt mentioned above may be a lithium salt, and the lithium salt is a substance that dissolves well in the non-aqueous electrolyte; for example, as the anion of the lithium salt, F - , Cl - , I- , NO3 - , N(CN)2 - , BF4 - , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , CF3SO3 - , CF3CF2SO3 - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - and (CF3CF2SO2)2N - One or more types selected from the group consisting of can be used.

[0121] In addition to the above electrolyte components, the above electrolyte may further include one or more additives for the purpose of improving the lifespan characteristics of the battery, suppressing the decrease in battery capacity, and improving the discharge capacity of the battery, such as, for example, a haloalkylene carbonate-based compound such as difluoroethylene carbonate, pyridine, triethylphosphite, triethanolamine, cyclic ether, ethylene diamine, n-glyme, triamide hexaphosphate, nitrobenzene derivative, sulfur, quinone imine dye, N-substituted oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol, or aluminum trichloride.

[0123] Examples

[0124] Hereinafter, embodiments of the present invention are described in detail so that those skilled in the art can easily implement the invention. However, the present invention may be embodied in various different forms and is not limited to the embodiments described herein.

[0126] Examples 1a to 4a and Comparative Examples 1a to 9a: Conductive material dispersion

[0127] 1 part by weight of a single-walled carbon nanotube bundle, 1 part by weight of polyvinylpyrrolidone (PVP, K15, Zhangzhou Huafu Co.) as a dispersant, and 200 parts by weight of N-methylpyrrolidone were mixed, and then first mixed for 180 minutes using a mixer (BTM-50, disper 1000 rpm / anchor 100 rpm). The conductive material dispersion obtained by varying the number of cycles using a high-pressure homogenizer (NG-20K, Genizer Co.) on the above mixture was secondarily mixed with different mixing ratios as shown in Table 1 below, thereby obtaining a dispersion containing SWCNT clusters with a solid content of 1 wt%.

[0128] Pressure Index* Weight ratio of dispersion by number of cycles 10 passes 5 passes 2 passes Example 1a 100 7 3 - Example 2a 100 6 4 - Example 3a 100 6.5 3 0.5 Example 4a 130 - 5 5 Comparative Example 1a 170 7 3 - Comparative Example 2a 170 8 - 2 Comparative Example 3a 100 - 2 8 Comparative Example 4a 130 - 3 7 Comparative Example 5a 100 4 4 2 Comparative Example 6a 100 2 2 6 Comparative Example 7a 100 1 2 7 Comparative Example 8a 100 1 1 8 Comparative Example 9a 170 9 1 -

[0129] * For the pressure applied to each, the pressure of Example 1 is considered as 100, and the value represents a relative value based on this.

[0131] Experimental Example 1: Measurement of Length and Particle Size

[0132] After diluting the conductive material dispersions of the above examples and comparative examples with water, 50 µl of the diluted solution was applied dropwise to the surface of freshly cleaved mica immediately after cutting, and then vacuum-dried to prepare a sample. The prepared sample was imaged using an atomic force microscope (AFM) (Asylum Research, Cypher ES AFM System) under the following conditions.

[0133] - Measurement mode: AC Air Topography mode (Tapping mode)

[0134] - Measurement conditions: Set point 0.4 V, Scan rate 1.5 Hz

[0135] - Measurement image size: Measured at 20 µm x 20 µm, 15 µm x 15 µm, and 10 µm x 10 µm magnifications

[0136] - Probe: AC160TS (n-type doped Si, reflective Al coating, f 0300 kHz, k 26 N / m)

[0137] After obtaining a length distribution map by measuring the length and diameter of more than 100 SWCNT clusters using an AFM image obtained under the above conditions (using an image processing program), the number average length and diameter, the ratio of the number of SWCNT clusters with a length exceeding 10 μm, and the ratio of the number of SWCNT clusters with a diameter exceeding 30 nm were derived.

[0138] Volume cumulative average particle size D 50 (㎛) and D 90 (㎛) was measured by introducing the above conductive material dispersion into a laser diffraction particle size measuring device (Mastersizer 2000, Malvern) and irradiating it with ultrasound of about 28 kHz at an output of 60 W, obtaining a volume cumulative particle size distribution graph, and then determining the particle size corresponding to 50% of the volume cumulative amount.

[0139] Number average length (㎛) Number ratio of lengths exceeding 10 µm Number average diameter (nm) Number ratio of diameters exceeding 30 nm D 50 (㎛) D 90 (㎛) Example 1a 1.54 1.0 9 3 3.6 12.1 Example 2a 1.72 1.5 10 4 3.5 15.8 Example 3a 2.30 3.9 17 6 3.8 20.1 Example 4a 4.20 7.8 21 9 3.8 28.1 Comparative Example 1a 0.68 0 4 3 3.4 15.8 Comparative Example 2a 0.71 0.2 6 5 3.5 15.5 Comparative Example 3a 7.10 22.0 38 21 28.0 92.0 Comparative Example 4a 3.00 7.0 32 10 3.9 25.0 Comparative Example 5a 2.00 6.0 20 15 3.1 23.0 Comparative Example 6a 3.00 7.0 29 13 3.9 28.0 Comparative Example 7a 9.00 8.0 25 10 8.0 43.0 Comparative Example 8a 2.00 30.0 25 10 23.0 85.0 Comparative Example 9a 0.60 5.0 3 3 3.5 19.0

[0140] Referring to Table 2 above, the volumetric cumulative average particle size D in the dispersion phase 50 and D 90 Even though the values ​​appear similar, it can be confirmed that the actual length of the SWCNT clusters included in the electrode is different.

[0142] Examples 1b to 4b and Comparative Examples 1b to 9b

[0143] Average particle size (D) of the negative electrode active material 50A cathode slurry with a solid content of 30% was prepared by mixing pure Si particles with a thickness of 5 μm, a particulate conductive material (SFG6L), each conductive material dispersion prepared in Examples 1a to 4a and Comparative Examples 1a to 9a (based on solid content weight), and a water-based binder in a weight ratio of 80:9.6:0.8:9.6 and using water as a solvent. Here, the water-based binder is a polymer obtained by polymerizing acrylamide, acrylic acid, and acrylonitrile in a weight ratio of 60:30:10 (polymerization reaction using ammonium persulfate polymerization initiator, 75°C, for 8 hours).

[0144] The above cathode slurry was coated onto one side of a copper foil with a thickness of 18 μm to form an active material layer with a thickness of 50 μm, and then dried to produce a cathode.

[0146] Experimental Example 2: Evaluation of Coating Processability and Lifespan Characteristics

[0147] An electrode assembly was manufactured by interposing a porous polyethylene separator between the negative electrode and the positive electrode of Examples 1b to 4b and Comparative Examples 1b to 9b, and after placing the assembly inside a case, an electrolyte was injected to manufacture a lithium secondary battery.

[0148] At this time, the electrolyte was prepared by dissolving 1 M concentration of LiPF6 in an organic solvent of ethylene carbonate / ethylmethyl carbonate / diethyl carbonate in a volume ratio of 3:4:4, and the anode was prepared as follows.

[0149] The above anode is LiNi 0.6 Co 0.1 Mn 0.3 O2, polyvinylidene fluoride, and carbon black were added in a weight ratio of 95:3:2, and N-methylpyrrolidone (NMP) was additionally added to prepare an anode slurry with a solid content of 70.1 wt%. Then, the anode slurry was applied onto an Al thin film current collector with a thickness of 20 μm, dried at 130°C, and rolled to produce the product.

[0150] The above lithium secondary battery was charged to 4.2V at a 0.1C C-rate, and then discharged to 2.5V to proceed with the activation process.

[0151] For each of the above lithium secondary batteries, the capacity retention rate was calculated by measuring the charge / discharge capacity while performing 100 charge / discharge cycles, with one cycle consisting of charging to 4.25V at 0.2C in CCCV mode (ending current 1 / 20C), charging to 4.25V at 45℃ with a constant current of 0.33C, and discharging to 2.5V with a constant current of 0.33C. The capacity retention rate was calculated as follows.

[0152] Capacity Retention Rate (%) = (Discharge Capacity after 100 cycles) / (Discharge Capacity after 1 cycle) × 100

[0153] Coating processability was evaluated by checking for stains on the electrode surface, pinholes, and clogging of the filter in the slurry circulation pump when coating the cathode slurry onto the copper foil, and was rated as X if any of these problems occurred and O if no problems occurred.

[0154] cathode Capacity retention rate (%) Electrode coating properties Example 1b 82 O Example 2b 85 O Example 3b 86 O Example 4b 85 O Comparative Example 1b 62 O Comparative Example 2b 68 O Comparative Example 3b 75 X Comparative Example 4b 72 O Comparative Example 5b 70 O Comparative Example 6b 71 O Comparative Example 7b 77 O Comparative Example 8b 72 X Comparative Example 9b 65 O

[0155] Referring to Table 3 above, it can be confirmed that when the cathodes of Examples 1b to 4b were applied, no problems occurred during the coating process, and the capacity retention rate was also excellent. However, when the cathodes of Comparative Examples 1b and 2b were applied, the capacity retention rate was about 20% worse than that of the Examples, which can be described as a difference in performance that cannot be distinguished by the particle size distribution of the conductive material dispersion.

[0156] Specifically, the results of Comparative Examples 1b and 2b above indicate that even if the particle size in the dispersion is identified as appropriate, the actual length of the SWCNT cluster is too short to properly form a conductive path, and thus can be said to be results showing that performance can be improved when the conductive material dispersion according to the present invention has characteristics.

[0157] In addition, it can be confirmed that when the cathode of Comparative Example 3b is applied, there is an excess of long SWCNT clusters and the number average length is also long, causing problems in the coating process.

[0158] In addition, when the cathode of Comparative Example 4b was applied, although the length characteristics were satisfied, it can be seen that no problems occurred during dispersion as the particle size characteristics in the dispersion solution were not significantly different from the example in that the number average diameter was large relative to the length of the SWCNT clusters; however, it can be confirmed that the capacity retention rate was low as a result of not forming a conductive network well overall within the electrode due to the relatively large diameter relative to the length. Comparative Examples 5b and 6b were confirmed to show similar results to Comparative Example 4b as there was a relatively excessive amount of SWCNT clusters with thick diameters.

[0159] Furthermore, it can be seen that when the cathode of Comparative Example 7b is applied, although the number of long SWCNT clusters is small, the possibility of dispersion problems is expected to be higher compared to when the cathode of Example 4b is applied due to the difference in number average length, and the capacity retention rate is also found to be about 10% inferior.

[0160] It can be confirmed that Comparative Example 8b causes problems in the dispersion phase and coating processability due to the excessive presence of long SWCNT clusters, similar to the case where the cathode of Comparative Example 3b is applied. In the case where the cathode of Comparative Example 9b is applied, judging by the very poor capacity retention rate, it can be inferred that the conductive network was not formed normally because the length was short and the diameter was thin.

Claims

Claim 1 A conductive dispersion comprising single-walled carbon nanotube (SWCNT) clusters, wherein the SWCNT clusters have a number average length of 0.8 μm to 8.0 μm, and SWCNT clusters with a length exceeding 10 μm account for 15% or less of the total number, the number average diameter of 5 nm to 25 nm, and SWCNT clusters with a diameter exceeding 30 nm account for 15% or less of the total number, and the length and diameter of the SWCNT clusters are measured using an atomic force microscope. Claim 2 The conductive material dispersion of claim 1, wherein the SWCNT cluster has a number average length of 1.0 μm to 6.0 μm. Claim 3 A conductive dispersion according to claim 1, wherein the SWCNT clusters comprise SWCNT clusters having a length exceeding 10 μm, which make up 10% or less of the total number. Claim 4 The conductive dispersion of claim 1, wherein the SWCNT cluster has a number average diameter of 7 nm to 20 nm. Claim 5 A conductive dispersion according to claim 1, wherein the SWCNT clusters comprise 10% or less of the total number of SWCNT clusters having a diameter exceeding 30 nm. Claim 6 The conductive material dispersion of claim 1, wherein the conductive material dispersion further comprises a dispersant, and the dispersant comprises one or more selected from the group consisting of polyacrylate, polyvinylidene fluoride, polyvinylpyrrolidone, polyvinyl alcohol, polyacrylamide, polyethylene oxide, carboxymethylcellulose, and diisopropylamine. Claim 7 A conductive material dispersion according to claim 6, comprising 0.2 to 3.5 parts by weight of SWNT clusters and 0.2 to 7.0 parts by weight of a dispersant, based on 100 parts by weight of the conductive material dispersion. Claim 8 An electrode active material layer comprising an electrode active material, a single-walled carbon nanotube (SWCNT) cluster, and a binder is disposed on a current collector, wherein the SWCNT cluster has a number average length of 0.8 μm to 8.0 μm, and SWCNT clusters with a length exceeding 10 μm account for 15% or less of the total number, and SWCNT clusters with a number average diameter of 5 nm to 30 nm account for 15% or less of the total number, and the length and diameter of the SWCNT cluster are measured using an atomic force microscope. Claim 9 The electrode according to claim 8, wherein the electrode active material is a positive electrode active material, and the positive electrode active material comprises one or more selected from the group consisting of lithium nickel-ternary oxide, lithium manganese oxide, lithium iron phosphate, lithium nickel oxide, lithium cobalt oxide and lithium manganese oxide. Claim 10 The electrode according to claim 8, wherein the electrode active material is a negative electrode active material, and the negative electrode active material comprises one or more selected from the group consisting of carbon-based particles, silicon-based particles, and carbon-silicon-based composite particles. Claim 11 The electrode of claim 8, wherein the electrode further comprises a dot-shaped conductive material, and the dot-shaped conductive material comprises carbon black. Claim 12 A lithium secondary battery having a structure in which a positive electrode, a separator, and a negative electrode are sequentially stacked, wherein at least one of the positive electrode and the negative electrode is an electrode according to claim 8.

Citation Information

Patent Citations

  • Conductive materail negative dispersed liquid, negative electrode prepared using same and rechargeable lithium battery including negative electrode

    KR1020230048929A